(3QSGdI PcQ GdQO Ydi Cgd GdJChjds - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdPjf jhLHhf JcQGQ GdBdg ai GdGbeUg eNJdaI jbGd dge gPG GdEdg YGOd Ce LGFQ XGde s
(3BNQgG (B:s
(3hRGd Yf bdHg GdYdhe GdhgejGJ GdeaSOg ddUhQ GdQhMGfjGJ hGdedMbI dg HYGde GdMjhGfjGJ hgh MSHi hKbJi HGdbGFe hcai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbHjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis